Benevolent and hostile sexism differentially predicted by facets of right-wing authoritarianism and social dominance orientation. (1st March 2019) - Austin, Darren E.J.; Jackson, Mervyn
Abstract: Despite progress towards equality on many fronts, sexism remains a problem. If sexism is to be combatted, an understanding of the attitudes underlying its various expressions is required. Previous research has strongly linked sexism to right-wing authoritarianism (a preference for collective security) and social dominance orientation (a preference for group-based hierarchy). Both are often considered unitary constructs, however recent attention to their facets has revealed finer details. This study breaks ground by utilising these facets to predict benevolent sexism (paternalistic attitudes towards women) and hostile sexism (antipathy towards women) in an Australian sample ( N = 229). Both sexism variables were significantly predicted by two of the five attitude facets. For benevolent sexism, these were traditionalism and dominance, and for hostile sexism, they were conservatism and anti-egalitarianism. Hostile sexism was also predicted by gender. These findings add to the theoretical understanding of ambivalent sexism, have implications for addressing sexism in society, and support calls for future research to utilise the facets of right-wing authoritarianism and social dominance orientation.